Attitudes toward and the Current Adoption and Future Expectations of Working from Home in Hong Kong during the COVID-19 Pandemic - Xin Ping Loh; Yongsung Lee (Findings)
This study employs a dataset from the Hong Kong Mobility Survey to investigate attitudes towards working from home (WFH) among 901 workers in Hong Kong. A latent-class cluster analysis identified three clusters, each of which displays distinctive attitudes towards WFH. Those with positive attitudes tend to have a higher frequency of WFH while those with negative attitudes tend to have a lower frequency. Near-future expectations, however, do not appear to be affected by differences in attitudes toward WFH.